Biaxial Tensile Mechanical Properties of HTPB Solid Propellant - Li Jin; Qinzhi Fang; Xingwei Yan; Qinwei Hu (International Journal of Aerospace Engineering)
The purpose of this work is to study the effects of different loading rate ratios and loading speeds on the biaxial tension of hydroxyl-terminated polybutadiene (HTPB) solid propellant. A proper kind of biaxial tensile specimen with which the stresses in its central part can be obtained with the loads acted on each loading direction is designed and used in the study, and the strains in its central parts are obtained with the digital image correlation (DIC) method. The stress and strain relationship at each direction can be obtained by experiments. The uniaxial stress vs. strain curves and the biaxial stress vs. strain curves were obtained, and it was found that the loading speed remarkably influenced the biaxial tensile behaviors of HTPB propellant. The Mises equivalent stress and strain could be used to describe the biaxial tension stress and strain state, and the exponential constitutive model obtained in the study could be used to predict the stress vs. strain curve under different test conditions.